Influence of Annual Plant Diversity on Forage Productivity and Nutrition, Soil Chemistry, and Soil Microbial Communities - Bainard, Luke D.; Evans, Bianca; Malis, Erin; Yang, Tony; Bainard, Jillian D. (Frontiers in Sustainable Food Systems, 2020)
Forage cover crops are gaining in popularity on the Canadian prairies, where multi-species crop mixtures are grown for soil and ecosystem enhancing benefits, but also harvested for forage. As the use of these forage mixtures increases, more knowledge is needed to understand the impact these mixtures have on forage production systems. The objective of this study was to determine the effects of increasing plant species diversity on forage productivity, soil chemistry, and soil microbial communities. Field trials were conducted in 2016 and 2017 at two separate locations in the Canadian Prairie region that included four treatments: (1) oat monoculture, (2) three spp. mixture (one grass, one legume, one brassica), (3) six spp. mixture (two grasses, two legumes, two brassicas), and (4) nine spp. mixture (three grasses, three legumes, three brassicas). Soil and plant samples were collected at the mid and late growing season to assess soil chemistry, plant biomass and composition, forage nutrition and quality, and soil bacterial and fungal communities. Overall, the oat monoculture had the highest biomass productivity, while the nine spp. mixture produced the lowest biomass among the treatments. All three mixtures had a better nutritional profile [i.e., greater concentrations of Ca, Cu, Fe, total Kjeldahl nitrogen (TKN), total phosphorus (TP) and total potassium (TK), and lower concentrations of acid detergent fiber (ADF) and neutral detergent fiber (NDF)] compared to the monoculture. Differences in forage nutrition were particularly heightened at the end of the growing season. Soil chemical properties did not differ greatly among the treatments with the exception of higher levels of soil nitrate availability in the mixtures compared to the monoculture. Early indicators of a shift in soil microbial diversity and fungal community composition, and an increased abundance of fungal pathotrophs in the mixtures compared to the oat monoculture, was observed at one of the field sites. This study indicates that increasing plant species diversity does not always lead to an increase in biomass production or significant changes or improvements in soil microbial communities. However, the inclusion of multiple plant species can improve the quality and nutritive value of forages over a monoculture forage crop.